Comprehensive Modernization of Railway Transport as an Innovative Efficient Instrument to Raise Competitive Capacity of a Company - Logutova, T.; Poltoratskyi, M. (Економічний вісник Донбасу, 2015)
The article considers theoretical and practical aspects of modernization of railway transport owned by industrial and transport companies that will allow to raise competitive capacity of the companies due to decrease in value of finished products. It is substantiated a list of advantages when choosing comprehensive modernization as the efficient instrument to raise benefits from railway transport operation by industrial and transport companies. В статті розглянуто теоретичні та практичні аспекти оновлення основних засобів залізничного транспорту промислових і транспортних підприємств, що дозволить підвищити конкурентоспроможність підприємств за рахунок зниження вартості готової продукції. Обґрунтовано перелік переваг при виборі комплексної модернізації, як дієвого інструменту підвищення ефективності функціонування залізничного транспорту промислових і транспортних підприємств. В статье рассмотрены теоретические и практические аспекты обновления основных средств железнодорожного транспорта промышленных и транспортных предприятий, которые позволят повысить конкурентоспособность предприятий за счет снижения стоимости готовой продукции. Обоснован перечень преимуществ при выборе комплексной модернизации, как действенного инструмента повышения эффективности функционирования железнодорожного транспорта промышленных и транспортных предприятий.